2017
DOI: 10.1016/j.molbiopara.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium falciparum exported protein PF3D7_0402000 binds to erythrocyte ankyrin and band 4.1

Abstract: Plasmodium falciparum extensively modifies the infected red blood cell (RBC), resulting in changes in deformability, shape and surface properties. These alterations suggest that the RBC cytoskeleton is a major target for modification during infection. However, the molecular mechanisms leading to these changes are largely unknown. To begin to address this question, we screened for exported P. falciparum proteins that bound to the erythrocyte cytoskeleton proteins ankyrin 1 (ANK1) and band 4.1 (4.1R), which form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…Ankirin is also targeted by KAHRP 6 and other P . falciparum proteins 47 , 48 . Indeed, a previous study that analyzed the evolution of genes that interact with Apicomplexa parasites indicated that SPTB and ANK1 display features suggestive of adaptive evolution in mammals 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Ankirin is also targeted by KAHRP 6 and other P . falciparum proteins 47 , 48 . Indeed, a previous study that analyzed the evolution of genes that interact with Apicomplexa parasites indicated that SPTB and ANK1 display features suggestive of adaptive evolution in mammals 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Resolved protein bands were visualized after staining with Coomassie Brilliant Blue (CBB). Bands were excised and prepared for liquid chromatography-tandem mass spectrometry (LC-MS/MS) as described in [35] and Shakya et al (submitted). Erythrocyte cytoskeleton proteins that bound to purified MBP-PF3D7_0402100 were identified as described in Shakya et al (submitted).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Split-luciferase assays were performed as previously described ( [35,39] and Shakya et al submitted). Kinetic split-luciferase assays were performed by adding N-FLuc-ankyrin to samples containing C-FLuc-MESA MEC construct and luciferase substrate in binding buffer.…”
Section: Split-luciferase Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…NOT1.2 is predominantly detected in the cytoplasm at schizont stage as shown in facilitates the interaction between spectrin and actin. PHISTa also interacts with erythrocyte ankyrin ANK1, which links spectrin to the erythrocyte membrane and reduces the deformability of iRBCs [262,263]. The function of the third exported protein, PF3D7_0831400 is unknown.…”
Section: Histonesmentioning
confidence: 99%